Orchidaceae Flora of Joinville, Santa Catarina, Brazil - Werner Siebje Mancinelli; Karin Esemann-Quadros (Acta Biológica Catarinense, 2021)
The objective of this work was to conduct a floristic study of Orchidaceae in the municipality of Joinville (Santa Catarina, Brazil), which occurred from 2006 to 2015. The municipality is mainly covered with Atlantic Forest between 0 and 1,335 m elevation. For the family, 211 species within 90 genera were recorded. The richest genera are Epidendrum (17 spp.), Pabstiella (15 spp.), Acianthera (14 spp.), Anathallis (8 spp.) and Octomeria (8 spp.). The majority of the species are epiphytes (82%), 11% are terrestrial, and the remaining 7% are hemi-epiphytes, rupicolous or myco-heterotrophic. Two species, Grobya guiselii and Homalopetalum joinvillense, are known only from Joinville.